2013
DOI: 10.18697/ajfand.56.11580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation containers on the chemical composition of fermented sesame (Sesamum indicum L) seeds

Abstract: The importance of utilizing oilseeds as complementary nutrient sources for human consumption has received considerable attention in recent years. There exists wide varieties of oil crops including sesame seed (Sesamum indicum L.), which are reported in literature to be rich in oil and nutrients; however, the presence of anti nutritional factors limits its uses. Processing grain using fermentation results in enhanced nutrition, stabilization of original raw materials, and detoxification of anti nutritional fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…The reduction of the specific volume of loaves with the supplementation of NSPS or A‐HMT SPS was due to effect of dilution on gluten content in the composite flours. The reduction of the gluten content in the composite flours may give the significant effect on the dough properties including less elasticity and smaller extensibility resulting in smaller loaf volume . Miyazaki et al reported that the substitution of heat‐moisture treated maize starch (HMT‐M) to wheat flour decreased the elasticity of the dough because the HMT‐M did not bind readily with gluten to form elastic dough, resulting in low specific volume of loaves.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of the specific volume of loaves with the supplementation of NSPS or A‐HMT SPS was due to effect of dilution on gluten content in the composite flours. The reduction of the gluten content in the composite flours may give the significant effect on the dough properties including less elasticity and smaller extensibility resulting in smaller loaf volume . Miyazaki et al reported that the substitution of heat‐moisture treated maize starch (HMT‐M) to wheat flour decreased the elasticity of the dough because the HMT‐M did not bind readily with gluten to form elastic dough, resulting in low specific volume of loaves.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of Nwosu [ 22 ] on asparagus beans ( Vigna sesquipedalis ) had earlier shown that soaking could effectively reduce phytate and cyanogenic glycosides. Additionally, Makinde et al [ 23 ] reported an oxalate reduction of between 21.69% and 29.64% when different parts of Sesamum indicum cultivars were soaked for 12 h.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of NFRs in the latter category can be improved by various processing methods [ 21 ]. While some processing methods can increase the cost of feed production (due to the extra energy needed for thermal and mechanical processing), soaking is one of the few low-cost and simplistic methods that can be used for the processing of NFRs [ 22 , 23 , 24 , 25 ]. However, compared to other methods, this appears to be the least researched for the detoxification of many NFRs, perhaps because they are thought to be ineffective against thermolabile antinutrients.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the mineral content could be explained by the decrease in the total polyphenol content, thus, increasing the availability of minerals during fermentation. Studies by Makinde and Akinoso (2013) have shown an increase in phosphorus and potassium after the 7 th day of fermentation of sesame seeds. Mohamed et al (2007) noted an increase (22mg/100g) of phosphorus during the millet fermentation.…”
Section: Determination Of Minerals Contentmentioning
confidence: 99%